Open‐label, randomized, comparative, phase III study on effects of reducing steroid use in combination with Palonosetron. Issue 7 (27th May 2015) - Komatsu, Yoshito; Okita, Kenji; Yuki, Satoshi; Furuhata, Tomohisa; Fukushima, Hiraku; Masuko, Hiroyuki; Kawamoto, Yasuyuki; Isobe, Hiroshi; Miyagishima, Takuto; Sasaki, Kazuaki; Nakamura, Michio; Ohsaki, Yoshinobu; et al.
<x xml:space="preserve">Abstract</x> The purpose of this study is to compare the efficacy of a single administration of dexamethasone (DEX) on day 1 against DEX administration on days 1–3 in combination with palonosetron (PALO), a second‐generation 5‐HT3 receptor antagonist, for chemotherapy‐induced nausea and vomiting (CINV) in non‐anthracycline and cyclophosphamide (AC) moderately‐emetogenic chemotherapy (MEC). This phase III trial was conducted with a multi‐center, randomized, open‐label, non‐inferiority design. Patients who received non‐AC MEC as an initial chemotherapy were randomly assigned to either a group administered PALO (0.75 mg, i.v.) and DEX (9.9 mg, i.v.) prior to chemotherapy (study treatment group), or a group administered additional DEX (8 mg, i.v. or p.o.) on days 2–3 (control group). The primary endpoint was complete response (CR) rate. The CR rate difference was estimated by logistic regression with allocation factors as covariates. The non‐inferiority margin was set at −15% (study treatment group − control group). From April 2011 to March 2013, 305 patients who received non‐AC MEC were randomly allocated to one of two study groups. Overall, the CR rate was 66.2% in the study treatment group (N = 151) and 63.6% in the control group (N = 154). PALO plus DEX day 1 was non‐inferior to PALO plus DEX days 1–3 (difference, 2.5%; 95% confidence interval [CI]: −7.8%–12.8%; P‐value for non‐inferiority test = 0.0004). There were no differences between the two groups in terms of complete control rate (64.9 vs 61.7%) and total control rate (49.7% vs 47.4%). Anti‐emetic DEX administration on days 2–3 may be eliminated when used in combination with PALO in patients receiving non‐AC MEC.